2022
DOI: 10.25026/jtpc.v6i2.457
|View full text |Cite
|
Sign up to set email alerts
|

The Potency of the Genus Uncaria from East Borneo for Herbal Medicine Purposes: A Mini-review

Abstract: Uncaria is a genus of plants that are widely distributed in the tropics. There are about 5 of the 38 species of this genus growing in the tropical rain forests of East Borneo, Indonesia. For a long time, Uncaria is commonly used as a traditional medicine to treat various diseases by the Dayak tribe in Kalimantan, traditional people believe that Uncaria may be cured cancer, tumors, mioms, and cycts. Based on previous studies, the activity of the genus Uncaria has been widely reported such as cytotoxic, antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It was reported that this plant had moderate activity on MCF-7 cancer cells with an IC50 of 22.74μg/ml. 25,26…”
Section: Cytotoxic Activity Of Fractions Against Mcf-7 Cellsmentioning
confidence: 99%
“…It was reported that this plant had moderate activity on MCF-7 cancer cells with an IC50 of 22.74μg/ml. 25,26…”
Section: Cytotoxic Activity Of Fractions Against Mcf-7 Cellsmentioning
confidence: 99%
“…The Uncaria genus has around 34 species that are geographically spread in tropical regions, specifically Asia, Africa and Southeast America [20], [22]. Recently, many studies have been conducted regarding the genus Uncaria and reported that plants of the genus Uncaria have various pharmacological effects [23], such as treating wounds and ulcers, fever, asthma, rheumatism, hyperpyrexia, anti-inflammatory, hypertension, antioxidant, gastrointestinal diseases, antibacterial, antifungal, antiprotozoal, antiviral, anticancer, anticonvulsant, antidepressant, antithrombotic, antidiabetic, stroke, epilepsy and neurodegenerative diseases [24 -30]. Based on phytochemical studies carried out, alkaloids are secondary metabolite compounds that are proven to be the most common and found in the genus Uncaria [26], [31 -34].…”
Section: Introductionmentioning
confidence: 99%
“…The water comes out from the cut stems, usually drunk, to increase or restore stamina while working in the forest. The dried powder of the stem is often used to treat scabs and wounds by sprinkling them on top of the wound, which has been practiced for hundreds of years (Almeida et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The potential for the development of leads from Uncaria continues to grow, particularly in the area of immunomodulatory, anti-inflammatory and vascular-related conditions (Heitzman et al, 2004;Zhang et al, 2015;Qin et al, 2021). Uncaria species that most studied are Uncaria gambir, Uncaria nervosa, Uncaria longiflora, Uncaria tomentosa, Uncaria cordata, Uncaria macrophylla, Uncaria rhynchophylla, and Uncaria hirsuta (Almeida et al, 2022;Munggari et al, 2022;Huang et al, 2021). Uncaria callophylla is one of the Uncaria species that is still under-researched.…”
Section: Introductionmentioning
confidence: 99%